The impact of IPO attributes, firm-level characteristics and ownership on Malaysian IPO firms’ earnings management - Kalgo, Sani Hussaini; Nahar, Hairul Suhaimi; Amin Noordin, Bany Ariffin (Penerbit Universiti Sains Malaysia, 2022)
The paper investigates Malaysian Initial Public Offering (IPO) firms’ financial reporting behaviour from the specific perspective of their earnings management (EM) practices covering both real (REM) and accrual (AEM) techniques. It further examines the impact of unique IPO attributes, firm level characteristics and ownership structure on both EM practices contemporaneously. Using the established and commonly used EM models to measure both AEM and REM for IPO firms from 2002 to 2013, the results indicate that IPO firms engage in both EM strategies around the corporate event. It also shows that such strategies are not just opportunistically motivated but attributable to several unique IPO attributes, firm level characteristics and ownership variables. The paper adds to the existing body of knowledge on IPO in the specific emerging country context of Malaysia which evidence from prior studies are observably scant.